Antibody dependent cellular phagocytosis by macrophages is a novel mechanism of action of elotuzumab - Kurdi, Ahmed T. (Mol Cancer Ther, 2018)
Elotuzumab, a recently approved antibody for the treatment of multiple myeloma (MM), has been shown to stimulate Fcγ receptor (FcγR)-mediated antibody-dependent cellular cytotoxicity (ADCC) by natural killer (NK) cells towards myeloma cells. The modulatory effects of elotuzumab on other effector cells in the tumor microenvironment, however, has not been fully explored. Antibody dependent cellular phagocytosis (ADCP) is a mechanism by which macrophages contribute to anti-tumor potency of monoclonal antibodies. Herein, we studied the NK cell independent effect of elotuzumab on tumor associated macrophages (TAMs) using a xenograft tumor model deficient in NK and adaptive immune cells. We demonstrate significant anti-tumor efficacy of single agent elotuzumab in immunocompromised xenograft models of multiple myeloma, which is in part mediated by Fc-FcγR interaction of elotuzumab with macrophages. Elotuzumab is shown in this study to induce phenotypic activation of macrophages in-vivo and mediates ADCP of myeloma cells though a FcγR dependent manner in-vitro. Together, these findings propose a novel immune mediated mechanism by which elotuzumab exerts anti-myeloma activity and helps to provide rationale for combination therapies that can enhance macrophage activity.